Hemochromatosis and Xeroderma Pigmentosum: Two (Un)Suspicious Neighbors - Monte,Filipa (2022)
Abstract A 51-year-old woman, clinically diagnosed with Xeroderma pigmentosum (XP), showed abnormalities in liver enzymes, high ferritin and transferrin saturation levels, with ultrasonographic features of chronic liver disease, in addition to skin hyperpigmentation. Genetic testing confirmed the clinical hypothesis of hereditary hemochromatosis (HH). Due to the known proximity of HFE (6p22.2) and POLH (6p21.1) genes, accountable for HH and the XP-V variant, respectively, a genetic test was offered and a rare variant of the POLH gene was identified. We report the first confirmed case, to our knowledge, of a patient diagnosed both with XP and HH, in whom two mutated neighbor genes - POLH and HFE - were identified, possibly the result of genetic linkage.